Meningkatkan Keterampilan Vokasional Membuat Bunga Mawar dari Sabun melalui Pendekatan Keterampilan Proses bagi Anak Tunagrahita Ringan - Nadia Syadza Yasmin; Mega Iswari (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
This study aims to analyze the method of mastering skills in one of the special schools (SLB) in Padang City, Indonesia. This study used a quantitative research method with a Single Subject Research (SRR) approach. All the data that the writer got were analyzed descriptively using graphical visual analysis tools. The results of this study prove that the use of the process skills approach can improve the skills possessed by children in learning, but it is necessary to develop further research on this issue in different contexts and issues.